2023
DOI: 10.3390/cells12202460
|View full text |Cite
|
Sign up to set email alerts
|

The G Protein-Coupled Estrogen Receptor (GPER): A Critical Therapeutic Target for Cancer

Keith A. Hall,
Edward J. Filardo

Abstract: Estrogens have been implicated in the pathogenesis of various cancers, with increasing concern regarding the overall rising incidence of disease and exposure to environmental estrogens. Estrogens, both endogenous and environmental, manifest their actions through intracellular and plasma membrane receptors, named ERα, ERβ, and GPER. Collectively, they act to promote a broad transcriptional response that is mediated through multiple regulatory enhancers, including estrogen response elements (EREs), serum respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 206 publications
(290 reference statements)
1
9
0
Order By: Relevance
“…2A-B) and T47D/PalbR (Additional File 2C) cells respect to their parental counterparts, in accordance with previous studies [65][66][67]. Considering that the estrogen receptor GPER mediates estrogenic signaling in different cell contexts [10,15,68], we aimed to evaluate whether the expression of GPER may be altered in palbociclib-resistant BC cells. Reminiscing previous RNAsequencing data [69], we found that the expression of GPER is increased at both the mRNA and protein levels in MCF7/PalbR (Fig.…”
Section: Palbociclib-resistant Bc Cells Display Increased Egfr and Gp...supporting
confidence: 58%
See 2 more Smart Citations
“…2A-B) and T47D/PalbR (Additional File 2C) cells respect to their parental counterparts, in accordance with previous studies [65][66][67]. Considering that the estrogen receptor GPER mediates estrogenic signaling in different cell contexts [10,15,68], we aimed to evaluate whether the expression of GPER may be altered in palbociclib-resistant BC cells. Reminiscing previous RNAsequencing data [69], we found that the expression of GPER is increased at both the mRNA and protein levels in MCF7/PalbR (Fig.…”
Section: Palbociclib-resistant Bc Cells Display Increased Egfr and Gp...supporting
confidence: 58%
“…The ligands are also shown separately: palbociclib (B), G-1 (C) and E2 (D). E ERK1/2 phosphorylation in CAFs transiently transfected with a control shRNA or a shGPER plasmid and then exposed for 15 Additional File 6B-C). Interestingly, palbociclib treatment reduced the viability only in MCF7 and T47D cells co-cultured with CAFs silenced for GPER expression (Fig.…”
Section: The Palbociclib-induced Regulation Of Pro-inflammatory Genes...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, even though in BALB– neu T mice, αER expression appears to be lost at an early stage of ErbB2/ neu -driven carcinogenesis, BPA can nonetheless promote tumor progression by acting via GPR30. Indeed, besides the well-known role of αER-mediated genomic and non-genomic pathways in enhancing breast cancer cell proliferation, survival, and invasion [ 65 , 66 ], a key role in estrogen-dependent responses and in the progression of breast cancer is played by GPR30 [ 67 , 68 , 69 , 70 ], and it has been previously demonstrated that GPR30 can mediate BPA estrogenic signals in ER-negative breast cancer cells [ 44 , 71 ]. While it is reported that about 60% of human breast cancers are positive for GPR30 expression [ 68 ], that mammary tumors of BALB– neu T mice express high levels of this alternative ER has not been reported before to our knowledge and highlights that these transgenic mice represent a valuable model to investigate the crosstalk between GPR30 and ErbB2/ neu in vivo [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…GPER has been demonstrated to play a pivotal role in various physiological and pathological processes across the immune, cardiovascular, endocrine, nervous, and reproductive systems [3,4]. Consequently, GPER is now recognized as a novel therapeutic target or prognostic marker in a range of pathologies, including cancer [8][9][10][11][12]. Here, we aim to provide a comprehensive summary of the current understanding of GPER's role in various cancer types.…”
Section: Introductionmentioning
confidence: 99%